Apoio cumputacional para teste de invasão em sistemas de comunicação de VANTs - Oliveira, Paulo Roberto de (2015)
In recent years, embedded systems have gained much space in the technological scenario, being intrinsically linked to products of daily life, such as the brake system of a car, the control of a washing machine, among others. There is also a more specific class called critical embedded systems. Such denomination is assigned because the high risk functions they perform. UAVs (Unmanned Aerial Vehicles) fall into this category and its security becomes an important aspect. Existing studies show that UAVs have communication system failures, which make them vulnerable to various types of attacks. Note that the security mechanisms are being used in a wrong way or absent in these aircrafts. Thus, this work conducted a broad survey of threats and vulnerabilities in UAVs, developed a general model for application of penetration testing on UAVs, along with a penetration testing software applied to simulated environments, which are presented as a step forward in the evolution of security UAVs environments.